Model driven design and evaluation of security level in orchestrated cloud services. (15th March 2018) - Amato, Flora; Mazzocca, Nicola; Moscato, Francesco
Abstract: Cloud-based architectures, services and resources are growing up in complexity day by day. Composition and Orchestration deal with the problem of creating complex services promoting reuse and optimal allocation of resources but many security issues arise complicating the work of designers. Even if any composing elements in a composition meets security requirements, the composite service may not. In order to reduce design and developing complexity, Big Vendors and scientific literature promote Composition by Patterns. In this work we present a Model Driven Engineering methodology that addresses validation and verification of security requirements by using formal methods and model transformation algorithms. We show how our model driven approach enables the specification of requirements at design phase and how it allows for verification of security requirements. Highlights: We present a MDE methodology addressing verification of security requirements by formal methods and model transformation. We show how our MDE methodology enables specification and verification of security requirements at design phase. Our Methodology is based on MetaMORP(h)OSy framework, Cloud Pattern definition and model transformation techniques. We enable Cloud Users to design by pattern. Pattern-based Specification is automatically translated into analyzable models. We show in a case study the application of the methodology to the Protection Reverse Proxy and Multi-Datacenter Patterns.